Cortical involvement in early Parkinson's disease: evidence from multimodal MRI - Klein, J; Rolinski, M; Griffanti, L; Szewczyk-Krolikowski, K; Baig, F; Ruffmann, C; Groves, A; Menke, R; Mackay, C; Hu, M (Wiley, 2017)
MRI studies in early Parkinson’s disease (PD) have shown promise in the detection of disease-related brain changes in vivo in the white and deep grey matter. While neuropsychology points to early cortical dysfunction even in early PD, MRI data on cortical involvement in early PD is lacking. We set out to establish if cortical pathology in early PD can be detected with MRI.